The promises and pains in procurement reforms in the Philippines - Adoracion M. Navarro; Juan Alfonso O. Tanghal (Philippine Institute for Development Studies (PIDS), 2017)
This study examines procurement policy issues in light of recent concerns on delays in project implementation and underspending of government agencies. In the 2014 and 2015 reports of the Department of Budget and Management, procurement is cited as a reason for underspending. Likewise, government agencies with major underspending concerns noted "public procurement issues" as a recurring reason for the low disbursement outturn. In an attempt to make procurement less of a hurdle, Congress currently proposes to grant emergency powers to the president and do away with competitive bidding as the default mode in implementing transportation projects. However, procurement data analysis shows that in civil works procurement, the bid failure rate tends to be higher under the alternative mode of procurement than under the competitive mode, a result which does not support Congress' proposal. Key lessons from experience are also investigated through interviews with various government agencies in the implementation and execution of the Philippine procurement process. The numerous key informant interviews greatly revealed the difficulties encountered and good practices implemented under the current legislative framework. To address procurement issues, the study recommends: (1) pursuing deliberate investments in and having a political will for systems change and organizational culture change, (2) greater investment in planning and other preparatory activities before the actual procurement, (3) innovation orientation in public procurement, and (4) value-for-money procurement.
Keywords: 330; procurement reforms; procurement law; competitive bidding; governance